EXPLORING THE SITE SELECTION OF INCENTIVE TRAVEL DESTINATION IN INDONESIA: A DUAL-MARKET PERSPECTIVE - Rossi, Fetty Nurmala; Octavanny, Vitha; Mbulu, Yustisia Pasfatima; Mashita, Azra (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study aims to explore the site selection of incentive travel destination as a key decision for Incentive travel housess and corporations in Indonesia, for both domestic and international markets. Site selection is a crucial aspect of planning because the destination serves not only as an event venue but also as a symbol of recognition, exclusivity, and corporate image for incentive participants. This study used a qualitative approach, combining field observations, semi structured interviews, and documentation study to identify location attributes for incentive destination. The findings indicate that Bali, Jakarta, and Yogyakarta have advantages in creating experiences and operational readiness, while Labuan Bajo, with its diverse natural resources, can create memorable experiences but requires significant operational improvement. Incentive travel housess and corporate buyers assessed that the domestic market's perspective favors destination selection based on accommodation, destination image, novelty, extra conference opportunities, and risk. However, for international market, there is more emphasis on accessibility, accommodation, destination image, uniqueness, extra conference opportunities, and risk. Only the Accessibility factor is the differentiator between the domestic and international markets, other attributes are not the main factors in either market but are supporting factors that complement the smoothness of incentive travel. The implication of this research is that it will make it easier for Incentive travel housess and corporations to make the right destination decisions for the domestic and international markets in Indonesia. In addition, this can serve as a recommendation to the Indonesian government for developing strategic policies and promoting other destinations as incentives.